Prenatal nitrate exposure from diet and drinking water and timing of puberty in sons and daughters: A nationwide cohort study. (December 2022) - Jul Clemmensen, Pernille; Brix, Nis; Schullehner, Jörg; Lunddorf, Lea Lykke Harrits; Ernst, Andreas; Ebdrup, Ninna Hinchely; Bjerregaard, Anne Ahrendt; Hansen, Birgitte; Thomas Stayner, Leslie; Ingi Halldorsson, Thorhallur; Frodi Olsen, Sjurdur; Sigsgaard, Torben; et al.
Graphical abstract: Abstract: Background: In Western countries, age at pubertal development has declined during the last century in girls, and probably also in boys. No studies have investigated whether nitrate, a widespread environmental exposure with teratogenic and hormone disrupting properties, might affect timing of puberty. Objectives: We investigated if prenatal exposure to nitrate from drinking water and diet was associated with timing of puberty. Methods: This cohort study included 15, 819 children born from 2000 to 2003 within the Danish National Birth Cohort. Self-reported information on current status of various pubertal milestones was provided every six months by a questionnaire from 11 years of age until 18 years or full maturity, whichever came first. Maternal nitrate intake from diet (mg/day) was derived from a mid-pregnancy food frequency questionnaire and individual level nitrate exposure from drinking water (mg/L) was derived using measurements from Danish public waterworks. Adjusted average differences in months in age at attaining several pubertal milestones as well as the average age difference in age at attaining all the milestones were estimated separately for diet and water using a regression model for interval-censored data. C- and E-vitamin, red meat and processed meat intake were explored as potential effect modifiers in sub-analyses. Results: No strong associations were observed between prenatal exposure to nitrate and timing of puberty in children. However, sons born of mothers with a nitrate concentration in drinking water at their residential address of > 25 mg/L (half of the World Health Organisation (WHO) guideline value) compared with ≤ 1 mg/L showed a tendency towards earlier age at pubertal development with an average age difference of −1.2 months (95 % confidence interval, −3.0;0.6) for all the pubertal milestones combined. Discussion: Studies including more highly exposed children are needed before the current WHO drinking water guideline value for nitrate can be considered safe concerning pubertal development.